Statistical analysis of regional integration effects - Olga Nosova (Universität Potsdam, Wirtschafts- und Sozialwissenschaftliche Fakultät, 2008)
The paper studies the regional integration as the unique process which depends on the degree of cooperation and interchange among regions. The generalisation of existing approaches for regional integration has been classified by the criterions. The data of the main economic indicators have been analysed. The economic analysis proves the differences in production endowments, the asymmetry in fixed capital investment, the disproportional income, and foreign direct investment distribution in 2001 2005 in Ukrainian regions. Econometric modelling depicts the existence of the division for the industrial regions with high urbanisation and backward agrarian regions in the Ukraine, the industrial development disparities among regions; the insufficient infrastructure (telecommunications, roads, hotels, services and etc.), the low labour productivity in industrial sector, and insufficient regional trade.
urn:nbn:de:kobv:517-opus-29106
Keywords: 330; regional integration; regions; economic disparities; Regionalentwicklung; Räumliche Interaktion; Regionales Cluster; Räumliche Verteilung; Räumliche Arbeitsteilung; Schätzung; Ukraine